Advances in the pyrolytic transformation of lignocellulosic biomass tophenol-enriched bio-oil - ZHAO Zhiyue; JIANG Zhiwei; ZENG Yongjian; YAN Kai* (能源环境保护, 2023)
With the increasing depletion of petrochemical resources and the environmental pollution caused by their consumption, the development and utilization of renewable resources have attracted extensive attention. Agroforestry biomass (ABS) is a low-cost, easily available and widely distributed renewable resource, which is mainly composed of cellulose, hemicellulose and lignin, and is a potential renewable energy resource. Pyrolysis of lignocellulosic biomass to phenol-enriched bio-oil is a promising application in the future. The pyrolysis methods, composition of lignocellulosic biomass, pyrolysis mechanism of main constituents of lignocellulosic biomass (cellulose, hemicellulose, lignin), and the effects of pyrolysis methods and catalyst type (active biochar, metal oxides, zeolite) on the phenols yield in the obtained bio-oil were discussed in detail. At last, the future research orientation of lignocellulosic biomass pyrolysis into phenol-enriched bio-oil was put forward based on some key questions to be solved. The formation of phenolics bio-oil via lignocellulosic biomass pyrolysis will provide a new path for the replacement of fossil energy, and provide theoretical support for the national "carbon peaking, carbon neutrality" goals.